Čekajući Godoa – I Dio
In the summer of 1993 Susan Sontag visited the besieged and destroyed city of Sarajevo to stage Samuel Beckett's play "Waiting for Godot" with a troupe of Sarajevo actors in a candlelit Sarajevo theatre. The tape contains the first part of the performance.